Effect of Carrot and Sweet Potato on the Storability of Chicken Nuggets during Refrigeration Storage - Bhosale, S. S.; Biswas, A. K.; Sahoo, J.; Chatli, M. K.; Sharma , D. K.; Devatkal, S.K. (Journal of Meat Science, 2011)
Chicken meat nuggets were prepared with ground raw carrot (10%) and mashed sweet potato (10%), individually aerobic packaged and stored at 4±1°C. Samples were evaluated for pH, free fatty acid (FFA) contents, 2-thiobarbituricacid reacting substances (TBARS), microbiological quality and sensory pro files at 5 days intervals during 25 days storage. Nuggets formulated with carrot and sweet potato affected (P<0.05) pH between control and treated samples. For each kind of sample, the pH values decreased (P<0.05) with storage days. Lipid oxidation products (FFA contents and TBARS numbers) though in creased with the increase of storage days, they were well below the acceptable limits at the end of the storage. Control samples had highest TBARS values. Both the formulated samples had a positive impact on product safety and quality, in respect to microbiological and sensory quality. In general, carrot and sweet potato is helpful to prevent lipid oxidation, improving microbiological quality as well as sensory attributes of the chicken nuggets.